2022
DOI: 10.1007/s10530-022-02764-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the life-history, development, and survival of spotted lantern fly in occupied and uninvaded ranges

Abstract: The Spotted Lantern Fly (SLF), Lycorma delicatula (Hemiptera: Fulgoridae), is a sap feeding pest native to southeast Asia that has become a global biosecurity threat following invasions into South Korea, Japan, and the United States in the last two decades. Environmental niche modelling has demonstrated considerable potential for further range expansions, including into Australia and Europe. Further analysis on the potential seasonal life-history and survival of this pest in its invasive range can inform monit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Several models have been developed to forecast the future spread and establishment potential of spotted lanternfly in the United States (Huron et al, 2022; Jones et al, 2022; Lewkiewicz et al, 2022; Wakie et al, 2020) and elsewhere (Jung et al, 2017; Maino et al, 2022). To ensure future models can be compared and combined through ensemble procedures, models should be based on the same historic and present spread data of spotted lanternfly.…”
Section: Discussionmentioning
confidence: 99%
“…Several models have been developed to forecast the future spread and establishment potential of spotted lanternfly in the United States (Huron et al, 2022; Jones et al, 2022; Lewkiewicz et al, 2022; Wakie et al, 2020) and elsewhere (Jung et al, 2017; Maino et al, 2022). To ensure future models can be compared and combined through ensemble procedures, models should be based on the same historic and present spread data of spotted lanternfly.…”
Section: Discussionmentioning
confidence: 99%
“…Current predictions of the potential spotted lanternfly geographic range have been based on their known distribution in cooler, more northern climates (Jung et al 2017, Namgung et al 2019, Wakie et al 2020, Maino et al 2021). At least one group of researchers, using data from these more northern geographic locations, suggested that there may be a lower latitude boundary for establishment due to the pest's intolerance to heat.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have been published that attempt to estimate the potential geographic range of spotted lanternfly in North America and around the world (Jung et al 2017, Namgung et al 2020, Wakie et al 2020, Maino et al 2021). Jung et al (2017) used CLIMEX software to generate an index of climatic suitability for SLF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been proposals encouraging the introduction of natural enemies from the insect's native environment: "Two parasitoid species have been discovered attacking spotted lanternfly, the attraction of A. orientalis to spotted lanternfly egg masses and successful rearing of these parasitoids make it a promising biological control agent." [10] This method seeks to leverage the evolutionary adaptations of predators and parasitoids coevolved with the SLF, creating a natural balance. While adopting this approach, meticulous consideration is crucial to prevent unintended ecological consequences, holding the potential for sustainable, long-term control.…”
Section: Options For Human Interventionmentioning
confidence: 99%